Професійна підготовка музикантів-виконавців в Музичній академії Загребського університету (Республіка Хорватія) - Шетеля Наталія; Shetelya Natalia; Черкасов Володимир; Cherkasov Volodymyr (Видавництво «Код», 2025)
Резюме. У статті доведено, що Музична академія Загребського університету підтримує високі стандарти та орієнтири у сфері вищої музичної освіти та уважається музичним центром з міжнародною репутацією, визнаним та бажаним місцем навчання та роботи студентів і професорів усього світу.

Abstract. The article proves that the Music Academy of the University of Zagreb supports high standards and guidelines in the field of higher music education and is considered a music center with an international reputation, a recognized and desirable place of study and work for students and professors from all over the world. The fundamental values of this vision are the creative and pedagogical quality of the teaching staff, innovation and continuous development of curricula, as well as the expansion of professional competences of graduates. Ensuring continuity and development in the field of musical art, the teaching staff of the Academy of Music forms an artistic and intellectual elite of young musicians who, through their creative activities, influence the development of world culture, Croatian musical art, and international society. The Academy of Music strives to set standards and benchmarks, as well as values, in all areas of higher music education and to become a music center with an international reputation, a recognized and desirable place to study and work for students and teachers around the world. The main values of this vision are the artistic and pedagogical quality of the teaching staff, innovation and continuous development of curricula, as well as the expansion of professional competencies of graduates. Ensuring continuity in the development of musical art, the Academy of Music forms an artistic and intellectual elite of young musicians who, through their public activities, will influence the development of culture and art for the benefit of the entire social community.
Professional training of musicians-performers at the Music Academy of the University of Zagreb (Republika Hrvatska)
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-15
Keywords: Музична академія Загребського університету; музиканти-виконавці; професійна підготовка